2003
DOI: 10.1071/wr02075
|View full text |Cite
|
Sign up to set email alerts
|

Frog ecology in modified Australian landscapes: a review

Abstract: Frog decline in Australia has often occurred where habitat is relatively intact. Habitat alteration and loss do, however, threaten many species. Widespread degradation of aquatic and terrestrial systems has occurred since European settlement, with only 6.4% of Australia's landmass reserved for conservation. But what do we know about how frogs use modified Australian landscapes? Do wildlife managers have the information required to ensure that frog habitat is considered in the management and revegetation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 116 publications
(103 reference statements)
0
38
3
1
Order By: Relevance
“…Irrespective of the explanation for regional differences in the effects of salinity, our findings are in agreement with the popular supposition that human-induced salinisation has had widespread negative impacts upon freshwater biodiversity (Semlitsch and Bodie 1998) In regard to the habitat variables examined, anuran species richness was not related to wetland size or the percentage of vegetation surrounding a wetland. These findings contrast with previous studies that have found these habitat variables to be reliable predictors of anuran species richness (Hazell 2003;Pillsbury and Miller 2008). However, in this study we did not expect a significant relationship between habitat characteristics and species richness because we purposely chose study sites with habitat characteristics known to support a diversity of Victorian anuran species (Cogger 2000).…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Irrespective of the explanation for regional differences in the effects of salinity, our findings are in agreement with the popular supposition that human-induced salinisation has had widespread negative impacts upon freshwater biodiversity (Semlitsch and Bodie 1998) In regard to the habitat variables examined, anuran species richness was not related to wetland size or the percentage of vegetation surrounding a wetland. These findings contrast with previous studies that have found these habitat variables to be reliable predictors of anuran species richness (Hazell 2003;Pillsbury and Miller 2008). However, in this study we did not expect a significant relationship between habitat characteristics and species richness because we purposely chose study sites with habitat characteristics known to support a diversity of Victorian anuran species (Cogger 2000).…”
Section: Discussioncontrasting
confidence: 55%
“…Previous studies have shown that anuran species richness can be significantly influenced by pond size and the amount of vegetation surrounding ponds (García-Muñoz et al 2010a;García-Muñoz et al 2010b;Glooschenko et al 1992;Hazell 2003). Therefore, at each study site we measured pond area (m 2 ) and estimated the amount of vegetation surrounding ponds (% cover in a 1km radius).…”
Section: Habitat Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a variety of other potential factors responsible for declines have been reported (Pechmann & Wilbur 1994;Hines et al 1999;McCallum 2005;Di Rosa et al 2007). Habitat fragmentation and degradation in particular poses one of the greatest threats to amphibians (Gibbons et al 2000;Hazell 2003;Cushman 2006;Becker et al 2007;Hamer & McDonnell 2008). …”
Section: Amphibian Declinesmentioning
confidence: 99%
“…Knutson et al (1999) found a negative association of anurans with the presence of urban land, and conclude that landscape habitat analyses can provide a framework for future research on factors affecting anuran conservation. Targeted research is essential, because landscape planning often consists of broad land use recommendations which target a range of species (Rutherfurd et al 2000), and does not incorporate the specific habitat needs of frogs (Hazell 2003) in both terrestrial and aquatic environments (Stebbins 1997), which are essential considerations for stream-associated anurans.…”
Section: Riparian Vegetation Conditionmentioning
confidence: 99%